Impacts of LOC105371267 Variants on Breast Cancer Susceptibility in Northern Chinese Han Females: A Population-Based Case-Control Study. (29th August 2021) - Peng, Linna; Huang, Congmei; Xing, Shishi; Li, Dandan; He, Chunjuan; He, Yongjun; Yang, Wei; Jin, Tianbo; Wang, Li
Abstract : Background . LOC105371267, also known as PR-lncRNA1, was reported to be a p53 -regulated long noncoding RNA (lncRNA), which played an essential role in the pathogenesis of breast cancer (BC). We aimed to observe the potential association between LOC105371267 polymorphisms and BC risk in Northern Chinese Han females. Methods . Totally, 555 healthy individuals and 561 patients with BC were recruited. Five candidate SNPs (rs6499221, rs3931698, rs8044565, rs3852740, and rs111577197) of LOC105371267 were genotyped with the Agena MassARRAY system. Odds ratio (OR) and 95% confidence intervals (CIs) were applied to evaluate the relationship of LOC105371267 genetic polymorphisms with BC susceptibility. Additionally, stratification analysis based on clinical features and haplotype analysis were also conducted. Finally, multifactor dimensionality reduction (MDR) analysis was performed to assess the SNP-SNP interaction among LOC105371267 variants, and false-positive report probability (FPRP) analysis was used to validate the result of this study. Results . In this study, rs3931698 was a protective factor of BC in total (GG homozygote: OR = 0.30, 95% CI: 0.11–0.82, p = 0.018 ; recessive model: OR = 0.30, 95% CI: 0.11–0.84, p = 0.021 ). In stratification analysis based on the average age of 52 years and clinical characteristics (PR status, III-IV TNM stage), rs3931698 was also demonstrated to be associated with BC susceptibility. In addition, rs6499221 and rs3852740 were also associated with BC susceptibility among patients at age <52 years and patients with BC in a positive status. Thus, the haplotype analysis had a negative result for the incidence of BC (p > 0.05 ), and haplotype consisting of rs8044565 and rs111577197 was nonsignificantly associated with the BC risk. Finally, MDR and FPRP analyses also validated the result of this study. Conclusion . Polymorphisms rs3931698, rs6499221, and rs3852740 of LOC105371267 were found to be associated with the risk of BC in total, and stratification analysis in the Northern Chinese Han females suggested that LOC105371267 variants might be helpful to predict BC progression.